Computing in mathematics education: Past, present, and future - Gadanidis, G. (2022)
In this chapter, we follow up on the call by Borba et al. (2014) for historical research to understand technology trends in education. We conduct a historical scan of the origin of Computing in Education. We start with the Logo movement led by Papert and present an overview of the implementation of Computing in Education, including a survey of the main technological resources used and talk about robotics in educational contexts. We continue by recognizing the growth of research on Computational Thinking worldwide and present a brief history of this type of thinking, as well as its characteristics. We also describe some current research that deals with this theme in Basic Education, from Early Childhood Education to High School. With this, we seek to indicate possible trends for research on Computational Thinking in Education and Mathematical Education, enabling a reflection on the future. Therefore, in the conclusion section, we provide a synthesis of what may be learned from the past and the present, so that we can look to the future of Mathematics Education with regard to the use of Computing in Basic Education.